Applying Human Factors Engineering Program to the Modernization Project of NPP Control Room in accordance with U.S.NRC and KTA Regulations (Brazilian Journal of Radiation Sciences, 2019)
Application of Human Factors Engineering (HFE) in the design and implementation of such a project is essential to ensure that the new man-machine interface outcoming from the modernization does not have any negative impacts on human performance and plant safety.This paper analyzes the applicability of the Human Factors Engineering Program in the licensing and certification of Konvoi Nucleoelectric Power Plant Control Room modernization Project using digital instrumentation and control in accordance with U.S.NRC and KRA regulations.The results of the analyses show that although regulatory bodies adopt different methodology in the process of licensing the modernization of control rooms, the engineering aspects are being developed based on the principles of engineering.
Keywords: Control Room; Human Factors Engineering Program; Regulations and Licensing.